Plasma microRNA profiling reveals loss of endothelial miR-126 and other microRNAs in type 2 diabetes - Zampetaki, Anna; Kiechl, Stefan; Drozdov, Ignat; Willeit, Peter; Mayr, Ursula; Prokopi, Marianna; Mayr, Agnes; Weger, Siegfried; Oberhollenzer, Friedrich; Bonora, Enzo; Shah, Ajay; Willeit, Johann; et al. (My University, 2010)
MicroRNAs (miRNAs) have been implicated in the epigenetic regulation of key metabolic, inflammatory, and antiangiogenic pathways in type 2 diabetes (DM) and may contribute to common disease complications.
Keywords: Diabetes mellitus; MicroRNA; Vascular endothelium